Namque canebat (ecl. 6.31): the song of Silenus in Virgil’s Eclogue 6 and the pantomime of Silenus in Nonnus’ Dionysiaca (19.263-286) - Karanikas, Panagiotis (Ariadne, 2026)
This study explores the performative and intergeneric dialogue between Virgil’s Eclogue 6 and Nonnus’ Dionysiaca (19.263–286), focusing on the figure of Silenus as both singer and pantomime performer. While previous scholarship has often assumed that Eclogue 6 was staged as a pantomime, this paper argues instead that Virgil consciously integrates pantomimic references within his bucolic poetry, transforming theatrical elements into literary commentary. By examining passages that evoke bodily motion, transformation, and performance, the article shows how Virgil’s Silenus enacts a poetic pantomime of cosmic and mythological metamorphosis. The discussion then turns to Nonnus’ description of the pantomimic contest between Maron and Silenus, a creative reception of Virgil that literalizes the performative potential of Eclogue 6. Nonnus presents Silenus’ dance as a kinetic narrative culminating in transformation and collapse, thus converting Virgil’s poetic choreography into actual stage movement. The comparison reveals how both poets engage with the aesthetics of embodiment and the fluid boundaries between song, dance, and text. Ultimately, the paper argues that Virgil’s “song” of Silenus and Nonnus’ “dance” of Silenus together illuminate a continuous tradition of literary references to pantomime, in which poetic form itself becomes a performative act.